A CORRELATIONAL STUDY OF ORGANIZATIONAL SAFETY CULTURE, EMPLOYEES’ SAFETY BEHAVIOR AND PRODUCTIVITY- A CASE STUDY OF ONGC, MAHARASHTRA - Kudkilwar, Moreshwar; Kulkarni, Nirzar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research seeks to establish a correlation between the safety culture of ONGC in Maharashtra and their employees’ safety attitude as well as their productivity profile. Conducting this study as a correlational research, quantitative research data was collected from a sample of the ONGC human resource through structured questionnaires. This study confirmed the hypothesis that the corporate safety culture that is strong and developed has an impact on employees’ safety behaviours’ improvement. Moreover, I found that enhanced safety behaviours have a direct impact on productivity in relation to the employees. This research helps to enhance the best practices of safety culture to improve organisational safety and efficiency in the integrated oil and gas industries more effectively. The conclusions made from the research have several managerial implications with regard to the improvement of safety measures, and the general performance of the organisation. Suggestions for the future works include examining other factors which can influence the safety culture and productivity relationship in similar industrial organisations.